Integrating the Principles of Sanghawatthutham to Enhance the Effectiveness of the Welfare of the Elderly in Waeng Nang Subdistrict Municipality, Mueang District, Maha Sarakham Province: Integrating the Principles of Sanghawatthutham to Enhance the Effectiveness of the Welfare of the Elderly in Waeng Nang Subdistrict Municipality, Mueang District, Maha Sarakham Province - Thewatejo (Tanason), Phra Adun; Phrakhrusutaworathammakit; Chantawaree, Sukanda (RATANABUTH JOURNAL, 2024)
This research aims to 1) To study the effectiveness level of the elderly welfare arrangement of Waeng Nang Subdistrict Municipality, Mueang District, Maha Sarakham Province. 2) To study the relationship between the principles of social welfare and the effectiveness of the welfare arrangements for the elderly of Waeng Nang Subdistrict Municipality, Mueang District, Maha Sarakham Province. 3) To study the integration approach of the principles of social welfare to promote the effectiveness of the elderly welfare arrangements of Waeng Nang Subdistrict Municipality, Mueang District, Maha Sarakham Province. Mixed-method research was conducted using quantitative. The sample group consisted of 290 elderly people aged 60 years and over in Waeng Nang Subdistrict Municipality, Mueang Maha Sarakham District, Maha Sarakham Province. Data were analyzed by finding frequency, percentage, mean, standard deviation and Pearson's product moment correlation coefficient and qualitative research by means of in-depth interviews with 12 key informants, analyzing data using content analysis techniques, including context and synthesizing data according to the research objectives. The following results were found: 1) The overall level of effectiveness in providing welfare for the elderly of Waeng Nang Subdistrict Municipality, Mueang District, Maha Sarakham Province is at a high level (X2= 3.91 S.D. = 0.21). When considering each aspect, it was found that it was at a high level in all aspects. 2) The results of the analysis of the relationship between the principles of social welfare and the enhancement of the effectiveness of the provision of welfare for the elderly in Waeng Nang Subdistrict Municipality, Mueang District, Maha Sarakham Province, overall, showed a low level of positive relationship (r = .337) with statistical significance at the 0.01 level, therefore, the hypothesis was rejected. 3) The effectiveness of the welfare arrangement for the elderly of Waeng Nang Subdistrict Municipality. The government should promote the elderly to have more access to state welfare, such as in medicine and public health. The government should promote the elderly to have access to the health system to support the aging society. The development of the elderly care model during the rehabilitation period should increase policies or organize training programs to provide knowledge, promote, support, protect and safeguard the elderly to access the welfare system equally and fairly.